Efï¬cient FPGA implementation of high speed digital delay for wideband beamforming using parallel architectures - Simone, Lorenzo; Cardarilli, Gian Carlo; Nunzio, Luca Di; Fazzolari, Rocco; Giardino, Daniele; Matta, Marco; Re, Marco; SpanÃ², Sergio (Bulletin of Electrical Engineering and Informatics, 2019)
In this paper, the authors present an FPGA implementation of a digital delay for beamforming applications. The digital delay is based on a Parallel Farrow Filter. Such architecture allows to reach a very high processing rate with wideband signals and it is suitable to be used with Time-Interleaved Analog to Digital Converters (TI-ADC). The proposed delay has been simulated in MATLAB, implemented on FPGA and characterized in terms of amplitude and phase response, maximum clock frequency and area.